Neuroscience-Based Board Game to Foster Environmental Awareness in Children Aged 5ÔÇô6 - Ayu Pratiwi, Ika; Priyanti, Nita (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to develop a neuroscience-based game board learning media to enhance environmental awareness in children aged 5-6 years at TK Islam Al-Amanah, Depok City. Using the Research and Development (R&D) approach with the AIDDIE model, the study involves five stages: analysis, design, development, implementation, and evaluation. The results indicate that the neuroscience-based learning media is effective in increasing children's environmental awareness, as evidenced by the increase in pretest scores (39.7) to posttest scores (64.1), with a gain of 24.4 points. The implementation of this media is expected to be an innovative solution in early childhood education and improve environmental awareness in young children.┬á┬á